1997
DOI: 10.1051/lait:1997538
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring proteolysis and cheese juice composition during ripening of Cheddar cheese made from microfiltered milk

Abstract: Summary -Cheddar cheeses were made from three types of cheese milks: HTST pasteurized milk (Past), thermized milk (TH) and MF milk, a mixture of skimmilk treated according to the Bactocatchf process and pasteurized cream. Bacterial flora development of MF and TH cheeses during ripening was similar with a high growth of species belonging to the Lb casei group and an increase of Lactococci enumeration. On the contrary, Le counts in Past cheeses decreased by 3 log. As expected, the mesophilic spore count was much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
4
13
1
Order By: Relevance
“…There is no good relationship between Na content determined in Cantal cheeses (7.8 and 7.5 g·kg -1 ) and the value calculated from juices (8.7 and 9.2 g·kg -1 ) but the observed difference is much less than in the same comparison made from the results of Roy et al [57] for Cheddar: 6.1 g·kg -1 in the direct determination in cheese and 4.0 g·kg -1 for the calculation from juice. As said by Mermet [49], it is likely that the cheese matrix induces more inaccuracy in the ICP (Inductively Coupled Plasma) analytical method used by Roy et al [57] than in the AAS (Atomic Absorption Spectrometry) method used in this study. The molar ratio (Na + K)/Cl in the Cantal cheeses and juices was close to 1 as it was in Cheddar (Tab.…”
Section: Main Physicochemical Characteristicscontrasting
confidence: 54%
See 1 more Smart Citation
“…There is no good relationship between Na content determined in Cantal cheeses (7.8 and 7.5 g·kg -1 ) and the value calculated from juices (8.7 and 9.2 g·kg -1 ) but the observed difference is much less than in the same comparison made from the results of Roy et al [57] for Cheddar: 6.1 g·kg -1 in the direct determination in cheese and 4.0 g·kg -1 for the calculation from juice. As said by Mermet [49], it is likely that the cheese matrix induces more inaccuracy in the ICP (Inductively Coupled Plasma) analytical method used by Roy et al [57] than in the AAS (Atomic Absorption Spectrometry) method used in this study. The molar ratio (Na + K)/Cl in the Cantal cheeses and juices was close to 1 as it was in Cheddar (Tab.…”
Section: Main Physicochemical Characteristicscontrasting
confidence: 54%
“…Total calcium content appeared to be greatly different in the two Cantal cheeses but the soluble Ca content in both juices was similar (7.6 and 7.8 g per 1000 g of water). From the data of Tables I and II, it can be calculated that the ratio Ca S /Ca T (values expressed per 1000 g of water) which is established in the ripened cheese, by (i) the couple kinetics of curd acidification -kinetics of curd drainage, (ii) the salting of the curd and (iii) the caseino-phosphopeptide solubilisation from the cheese matrix during ripening [33], reaches 42% in Cantal A, 41% in Cantal B, 42% and 50.4% in Cheddar according, respectively, to Hassan et al [33] and Roy et al [57] and only 33% in Emmental [62]. The molar Ca T /P T ratio in Cantal cheeses A and B are, respectively, 1.5 and 1.8 versus 1.2 in Cheddar and 1.07 in Emmental [42].…”
Section: Main Physicochemical Characteristicsmentioning
confidence: 97%
“…MF results in reduced cheese NSLAB counts, with reduced intensity of cheese flavour and aroma, secondary proteolysis and levels of short-chain volatile acids in Swiss-type cheeses [13] and lower populations of heterofermentative lactobacilli, propionic acid bacteria and enterococci than from raw milk or from pasteurised milk with added MF retentate. However, Roy et al [120] reported similar counts of Lactobacillus casei and lactococci in both MF and thermised milks but with a lower mesophillic spore count in the latter. Beuvier et al [13] reported that MF treatment of milk resulted in lower levels of hydrolysis of β-casein in cheeses than from pasteurised milk; however, Roy et al [120] proposed that heating of cream or skim milk during MF treatment increased hydrolysis of β-casein in Cheddar cheese, possibly due to activation of the plasminogen-plasmin activation system.…”
Section: Microfiltrationmentioning
confidence: 95%
“…However, Roy et al [120] reported similar counts of Lactobacillus casei and lactococci in both MF and thermised milks but with a lower mesophillic spore count in the latter. Beuvier et al [13] reported that MF treatment of milk resulted in lower levels of hydrolysis of β-casein in cheeses than from pasteurised milk; however, Roy et al [120] proposed that heating of cream or skim milk during MF treatment increased hydrolysis of β-casein in Cheddar cheese, possibly due to activation of the plasminogen-plasmin activation system. Further optimization is required to achieve desirable ripening characteristics of such cheeses.…”
Section: Microfiltrationmentioning
confidence: 95%
“…The microfiltration process for debacteriazation, marketed as the "Bactocatch" process [26,29,37] has proved to be suitable for manufacturing Grevé and Herrgårds cheese [25], Comté-type cheese [7], Swisstype cheese [6,9,10] and Cheddar cheese [28,33]. These investigations showed that the indigenous flora of milk can be significantly reduced by microfiltration, however, with the result that the overall aroma intensity of the cheeses compared to raw milk cheeses is less pronounced.…”
Section: Original Articlementioning
confidence: 99%